A New Methodology for Estimating the Output Gap in the United States - Alichi, Ali (IMF Working Papers; Working Paper ;, 2015)
The gap between potential and actual output-the output gap-is a key variable for policymaking. This paper adapts the methodology developed in Blagrave and others (2015) to estimate the path of output gap in the U.S. economy. The results show that the output gap has considerably shrunk since the Great Recession, but still remains negative. While the results are more robust than other existing methodologies, there is still significant uncertainty surrounding the estimates.